AB0508 Frequency of the American College of Rheumatology (ACR) Classification Criteria in A Group of Patients with Systemic Lupus Erythematosus (SLE) Deceased during A 6-Year Period. (10th June 2014) - Padjen, I.; Cerovec, M.; Mayer, M.; Ćorić, T.; Anić, B.
Abstract : Background: Although the number of fulfilled ACR criteria is not a feature of disease severity in patients with systemic lupus erythematosus (SLE), renal and neurologic involvement are associated with a severe disease course (1, 2). Objectives: Comparison of the number of fulfilled ACR criteria between SLE patients (a) deceased early and late during the disease course and (b) identified and not identified as deceased in the period from 2006 to 2011. Methods: Data were retrieved from our hospital-based registry of SLE patients. Patients with a clinical diagnosis of SLE and at least one visit to the Centre in the 2006-2011 period or death in the same period were analyzed. Deceased patients were identified using the registry and death certificates. The number of fulfilled ACR criteria was counted for each patient. The χ 2 test and Fisher exact test, as well as the Student t-test were used to evaluate differences between categorical and continuous variables, respectively. The study was approved by the hospital ethics committee. Results: The total number of SLE patients with at least one visit to the Centre between 2006 and 2011 identified from the registry was 702. The frequency of ACR criteria was available for 693/702 patients. We identified 48 deceased patients (31 females and 17 males): 28 using the registry and 20 using death certificates - the latter were lost to follow-up before 2006. Data on the year of diagnosis and fulfillment of ACR criteria were not available for 4 deceased patients. The length of follow-up in the observed group of deceased patients was 12.09±7.38 years. Only 9/44 patients died within the first 5 years following diagnosis (early death). The rest of observed patients (35/44) died later during the disease course. The number of fulfilled criteria in the early and late death group was 4.11±1.05 and 4.71±1.56, respectively (difference not statistically significant). No difference was observed between the fulfillment of each of the criteria, except for the malar rash (19/35 in the late death group vs. 1/9 in the early death group, p=0.027). The frequency of renal disorder and discoid rash was significantly higher in the deceased patient group compared to patients not identified as deceased (21/44 vs. 167/665, χ 2 =9.702, p=0.002 and 20/44 vs. 128/665, χ 2 =15.610, p<0.001). No difference in frequencies of other criteria was observed between these two groups. Conclusions: Renal disorder and discoid rash are more frequent among deceased SLE patients compared to patients not identified as deceased in the observed group. References: Mak A, Cheung MW, Chiew HJ, Liu Y, Ho RC. Global trend of survival and damage of systemic lupus erythematosus: meta-analysis and meta-regression of observational studies from the 1950s to 2000s. Semin Arthritis Rheum. 2012;41:830-9. Doria A, Iaccarino L, Ghirardello A, Zampieri S, Arienti S, Sarzi-Puttini P, Atzeni F, Piccoli A, Todesco S. Long-term prognosis and causes of death in systemic lupus erythematosus. Am J Med. 2006;119:700-6. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3838